PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN, KEWAJIBAN MORAL, DAN PERSEPSI WAJIB PAJAK TENTANG SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK REKLAME - Komala Dewi, A. A. Sri Intan; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
The way to increase local tax revenue is to increase tax compliance itself. This study is intended to determine whether the taxpayer awareness, quality of service, a moral obligation, and the perception of taxpayers on tax penalties affect compliance advertisement taxpayer in Badung Revenue Service.This study used incidental sampling technique in method determining sample  and the number of respondents were 84 taxpayers is determined by the formula Slovin. This study tested using multiple linear regressions were processed with SPSS for Windows version 20. Based on the analysis, the variables of taxpayer awareness, quality of service, a moral obligation, and the perception of taxpayers on tax penalties have a positive effect on tax compliance in paying taxes billboards in Badung regency Revenue Service.
Keywords: tax compliance, taxpayer awareness, moral obligation, quality of service, the perception of taxpayers on tax penalties